The Influence of Green Transformational Leadership, Career Development and Organizational Culture on Employee Engagement Mediated by Organizational Commitment - Ramadhan, Shiomy Suci Wulandari; Arijanto, Agus (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Organizations face significant challenges in the BANI era, including productivity issues, difficulties in culture building, and crises of employee trust. Only 21% of employees globally feel actively engaged at work. This study aims to examine the influence of Green Transformational Leadership, Career Development, and Organizational Culture on Employee Engagement, with Organizational Commitment as a mediating variable. The research was conducted at AirNav Indonesia, a State-Owned Enterprise (SOE) in the Air Navigation Service Sector. The population in this study includes all low-level employees categorized as non-managerial at AirNav Indonesia, totaling 1,062 employees, with a sample size of 278 employees. This study employs a quantitative method using Structural Equation Modeling–Partial Least Squares (SEM-PLS), assisted by SmartPLS 4 software. The results indicate that Green Transformational Leadership, Career Development, and Organizational Culture each have a positive and significant effect on Employee Engagement. Additionally, Organizational Commitment has a positive and significant effect on Employee Engagement. Furthermore, Green Transformational Leadership, Career Development, and Organizational Culture are positively and significantly associated with Organizational Commitment. As for the mediating role, Organizational Commitment is proven to partially mediate the relationship between Green Transformational Leadership, Career Development, and Organizational Culture on Employee Engagement. These findings indicate that sustainable and employee-oriented HR practices, particularly in green leadership, career development, and organizational culture, can enhance Employee Engagement and overall organizational performance.